Pathological functional impairment: Neuropsychological correlates of the shared variance between everyday functioning and brain volumetrics - Fellows, Robert P.; Bangen, Katherine J.; Graves, Lisa V.; Delano-Wood, Lisa; Bondi, Mark W. (Frontiers in Aging Neuroscience, 2022)
Objective: Given that several non-cognitive factors can contribute to difficulties with everyday functioning, examining the extent to which cognition is associated with brain-related changes in everyday functioning is critical to accurate characterization of cognitive disorders. In this study, we examined neuropsychological correlates of the shared variance between everyday functioning and pathological indicators of cognitive aging using MRI brain volumetrics. Participants and Methods: Participants were 600 adults aged 55 and older without dementia (432 cognitively normal; 168 mild cognitive impairment [MCI]) from the National Alzheimer’s Coordinating Center (NACC) cohort who underwent neuropsychological testing, informant-rated everyday functioning, and brain MRI scanning at baseline. The shared variance between everyday functioning and brain volumetrics (i.e., hippocampal volume, white matter hyperintensity volume) was extracted using the predicted value from multiple regression adjusting for normalized total brain volume. The shared variance was used as an indicator of pathological everyday functional impairment. The residual variance from the regression analysis was used to examine functional reserve. Results: Larger white matter hyperintensity volumes (p = .002) and smaller hippocampal volumes (p < .001) were significantly correlated with worse informant-rated everyday functioning. Among individuals with MCI, worse performances on delayed recall (p = .013) and category fluency (p = .012) were significantly correlated with pathological functional impairment in multiple regression analysis. In the cognitively normal group, only worse auditory working memory (i.e., digit span backward; p = .025) significantly correlated with pathological functioning. Functional reserve was inversely related to anxiety (p < .001) in the MCI group and was associated with depressive symptoms (p = .003) and apathy (p < .001) in the cognitively normal group. Conclusions: Subtle brain-related everyday functioning difficulties are evident in MCI and track with expected preclinical Alzheimer’s disease cognitive phenotypes in this largely amnestic sample. Our findings indicate that functional changes occur early in the disease process and that interventions to target neuropsychiatric symptoms may help to bolster functional reserve in those at risk.